Analisis Usahatani Padi Hibrida Varietas Mapan P05 Terhadap Pendapatan Petani (Studi Kasus Desa Susukan, Kecamatan Susukan, Kabupaten Banjarnegara) - Moh. Masnur; Widawati, Enny; Chandra, Jimmy; Heikal, Jerry; Hadi, Pramono; Rachmawatie, Srie Juli (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
This study examines the profitability of Mapan P05 hybrid rice farming and the impact of production costs on farmers' income in Susukan Village, Banjarnegara Regency, Indonesia. Employing a quantitative approach with a field survey design, data were collected from 78 Mapan P05 rice farmers through structured interviews. Descriptive and multiple linear regression analyses were utilized to analyze the data. The findings reveal that Mapan P05 rice farming in Susukan Village is profitable, with an average net income of 17.3 million Rupiah per hectare per cropping season. The regression analysis further elucidated the significant role of efficient resource allocation, particularly in labor (coefficient 1.389) and land preparation (coefficient 5.109) influence farmer income, in augmenting farmers' profitability. The empirical model derived is Y = -19,997,135 + 5,420X1 + 0,198X2 + 0,540X3 + 1,389X4 + 5,109X5 + e, where Y represents farmer income, X1 denotes seed costs, X2 signifies fertilizer expenses, X3 represents pesticide costs, X4 denotes labor costs, and X5 signifies land preparation costs. The regression analysis underscoring the importance of efficient labor utilization and optimal investment in land preparation to enhance the profitability of Mapan P05 rice farming. This study provides empirical evidence that adopting high-yielding varieties like Mapan P05 seed can bolster production and income for farmers. However, it also highlights that the success of rice farming is contingent upon other factors. Keywords: Banjarnegara, Hybrid Rice Farming, Mapan P05, Farmer Income, Agriculture Economic